The imagery of night: the significance of night in artistic images and philosophies - Matthews, Thomas (Rhodes University, Faculty of Humanities, Department of Fine Art, 1966)
Introduction: At first glance, darkness is merely the absence of light, and is therefore negative; hence the traditional equation of night with death, evil and the creatures of the underworld. But a closer study will reveal that darkness is also a positive force; examples can be cited from various cultures where darkness was thought to have given birth to light. The subterranean is the realm of fertility; the worshippers of Dionysius realised this, as did the followers of the world-wide cult of the Great Earth Mother. The realm of darkness is also the habitat of the mystic. In this essay, we will attempt to define the nature of nocturnal imagery, and to trace the various ways in which mankind has sought to reconcile himself with the powers of darkness.
Keywords: Night in art